ANALISIS PERILAKU KONSUMEN INDUSTRI TEKSTIL PAKAIAN JADI DALAM MENGAMBIL KEPUTUSAN PEMBELIAN PRODUK FASHION JINISO DI JAKARTA BARAT - Pricilia Aziza, Deva; Meidiana, Meidiana (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research aims to understand and analyze consumer behavior, driving factors, and purchase decisions regarding the local brand Jiniso in west jakarta. The background of this research is the development of the fashion industry in Indonesia over the past few decades, where local producers compete to offer similar types of fashion with different qualities. The research uses qualitative methods with primary and secondary data as sources of information. Data collection techniques include observation, interviews, documentation, and triangulation, involving 7 informarts. Data analysis was conducted descriptively. The result of this research indicate that consumer behavior in purchasing Jinision brand products tents to favor products that are of good quality and have an affordable price.